2008
DOI: 10.1111/j.1600-0765.2007.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin induces osteoprotegerin synthesis via phosphatidylinositol 3′‐kinase/mammalian target of rapamycin pathway in human periodontal ligament cells

Abstract: Thrombin induces OPG synthesis in HPDL cells post-transcriptionally, possibly through PAR-1. The regulation was through the PI3K/Akt and mTOR pathway. This finding suggests that thrombin may play a significant role in alveolar bone repair and homeostasis of periodontal tissue, partly through the OPG/RANKL system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 40 publications
1
21
0
7
Order By: Relevance
“…One can speculate that the vasodilatory property exerted by parstatin could have counter‐regulated its suppressive effects on angiogenesis because the resultant increased vascular permeability theoretically could have allowed normal deposition of extracellular matrix and cellular migration necessary for periodontal repair to occur. In addition, the periodontal tissue under repair expresses high levels of thrombin, which, mainly through PAR1 activation, plays several roles on tissue repair 10,29 . In fact, PAR1 mediates the angiogenic activity of thrombin through stimulation of VEGF release and suppression of endostatin 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can speculate that the vasodilatory property exerted by parstatin could have counter‐regulated its suppressive effects on angiogenesis because the resultant increased vascular permeability theoretically could have allowed normal deposition of extracellular matrix and cellular migration necessary for periodontal repair to occur. In addition, the periodontal tissue under repair expresses high levels of thrombin, which, mainly through PAR1 activation, plays several roles on tissue repair 10,29 . In fact, PAR1 mediates the angiogenic activity of thrombin through stimulation of VEGF release and suppression of endostatin 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PAR1 potential activators at the periodontal environment, as well as its expression by human gingival fibroblasts, gingival epithelial cells, periodontal ligament cells, osteoblasts, and monocytic cells, were demonstrated by several studies that implicated its role in bone repair and homeostasis of periodontal tissues, 3,8‐10 as well as proliferation of gingival fibroblasts 11 . However, little is known about the role of parstatin, released during PAR1 activation.…”
mentioning
confidence: 99%
“…Little information is available about PAR-mediated PI3K signaling in normal human keratinocytes with comparable cellular function, but our results indicate HOKs have a unique signaling system. It has been shown that thrombin signals via PI3K to induce osteoprotegerin in human periodontal ligament and VEGF in human pigment retinal epithelial cells [23,27]. In a recent study Minhajuddin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that PAR 1 activation has a tissue destructive profile, leading to the induction of proinflammatory mediators that regulate periodontal breakdown, while others highlighted its possible involvement with the repair of periodontal tissues [11, 12]. …”
Section: Biological Effects Of Par1 Activation In Periodontal Cellmentioning
confidence: 99%
“…The other evidence that links PAR 1 action to bone metabolism comes from the fact that in periodontal ligament cells, PAR 1 activation by thrombin induces the synthesis of osteoprotegerin, which is one of the key molecules that regulate bone homeostasis and prevent osteoclastogenesis [12]. Corroborating with these findings, a recent study found that the activation of PAR 1 in monocytic cells by plasmin diminished LPS-induced inflammatory osteoclastogenesis and bone resorption by inactivation of nuclear factor kappa beta (NF- κ B) [13].…”
Section: Biological Effects Of Par1 Activation In Periodontal Cellmentioning
confidence: 99%